Acquired vulvar lymphangioma: Report of two cases - Widyasari, Indah; Fathan, Hafiza; Wibawa, Larisa Paramitha; Cipto, Herman; Sampurna, Adhimukti T; Sirait, Sondang Pandjaitan (Journal of General - Procedural Dermatology and Venereology Indonesia, 2016)
Vulvar lymphangioma is a rare case and often being misdiagnosed as genital wart. This acquired disorder manifests as dilatation of superficial lymph vessel due to obstruction. It is caused by urogenital infection and most often occurs following surgery and radiotherapy of cervical cancer. The diagnosis is established based on clinical and histopathological features. Treatment aimed to eliminate the cause of obstruction. This article reports two cases of vulvar lymphangioma found in our Hospital. First case was a 43-year-old female with a history of surgery and radiation for cervical cancer 10 years ago presented with vesicular skin lesion in genital area, oozing copious clear fluid since 4 years ago. There are multiple lenticular vesicles containing clear fluid in vulvar area accompanied with bilateral lymphedema of lower extremities. Histopathological features demonstrated dilated superficial lymph vessels. Second case was a 44-year-old female with enlargement of lower abdomen with vesicular lesion containing clear fluid in genital area since 3 years ago. Abdominal USG showed enlarged inguinal lymph node. Histopathological features demonstrated dilated superficial lymph vessels. The treatment for both cases were gradual electrosurgery. In both cases,vulvar dermis’ superficial lymph node dilatation caused the skin lesions. Obstruction of lymph vessel due to radiation and surgery for cervical cancer in the first case and of inguinal lymph node in the second case lead to increased lymphatic pressure in the dermis and later on the dilatations. The treatment in both cases using electrical excision produced good responses; however, we should be attentive on recurrent case.